2016
DOI: 10.1142/s1230161216500189
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Violation of Svetlichny Inequality for a Broad Class of States

Abstract: The fact that several copies of a local quantum state — when processed together — can generate a nonlocal correlation, i.e. the superactivation of quantum nonlocality, is a well-known feature of quantum mechanics. Most of research results focused strongly on the bipartite scenario. In this paper we show that the activation of violation of Svetlichny inequality, reported for the first time in our previous paper, is not an exceptional phenomenon but holds for a broad class of quantum states as well for pure as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Taking the above considerations into account in our previous paper [7,8], we have shown that the violation of the Svetlichny inequality can be activated for a class of GHZ states. We considered GHZ states because for these states the maximum value of the Svetlichny operator for a single copy of the state was determined analytically in [1].…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Taking the above considerations into account in our previous paper [7,8], we have shown that the violation of the Svetlichny inequality can be activated for a class of GHZ states. We considered GHZ states because for these states the maximum value of the Svetlichny operator for a single copy of the state was determined analytically in [1].…”
Section: Introductionmentioning
confidence: 74%
“…The analytical formula for S (1) max (ρ GHZ ) as a function of parameters was found in [1]. In our previous papers [7,8], we have shown that there exist such GHZ states for which S (1) max (ρ GHZ ) < 4 while S (2) max (ρ ⊗2 GHZ ) > 4. Moreover, due to the very simple form of white noise, we were able to find S (1) max (ρ wnGHZ ) where…”
Section: Analysis Of the Superactivation Of The Svetlichny Inequalitymentioning
confidence: 85%
See 1 more Smart Citation